Выполните умножение 2(b+1)(b+3) (8+3x)(2y-1) (5b-1)(b^2-5b+1) (15a+27)(-5a-9) (m-2n)(m+2n-1) b(3b+1)(2b-5) (3+x)(-1-x) ^2 это квадратсрочно через 45 минут уберу
Выполните умножение
2(b+1)(b+3)
(8+3x)(2y-1)
(5b-1)(b^2-5b+1)
(15a+27)(-5a-9)
(m-2n)(m+2n-1)
b(3b+1)(2b-5)
(3+x)(-1-x)
^2 это квадрат
срочно через 45 минут уберу
Ответ(ы) на вопрос:
Гость
[latex]2(b+1)(b+3)=2(b^2+4b+3)=2b^2+8b+6\\(8+3x)(2y-1)=16y-3x+6xy-8\\(5b-1)(b^2-5b+1)=5b^3-26b^2+10b-1\\(15a+27)(-5a-9)=-3(5a+9)(5a+9)=-3(5a+9)^2=\\=-3\cdot(25a^2+90a+81)=-75a^2-270a-273\\(m-2n)(m+2n-1)=m^2-4n^2-m+2n\\b(3b+1)(2b-5)=b(6b^2-13b-5)=6b^3-13b^2-5b\\(3+x)(-1-x)=-x^2-4x-3[/latex]
Не нашли ответ?
Похожие вопросы